Asian American sexual politics : the construction of race, gender, and sexuality - Chou, Rosalind (Rowman & Littlefield, 2012)
Asian American Sexual Politics explores beauty, self-esteem, and sexual attraction among Asian Americans. Drawing on sixty in-depth interviews, the book shows how constructions of Asian American gender and sexuality reinforce the social and political dominance for whites and exposes often-ignored new racism in the United States.